#TITLE_ALTERNATIVE# - ZULFIKAR (NIM 10205041), ADITIA
There are various imaging methods that can be used in a cancer diagnostic process using modern equipments which based upon radiation principles, such as X-ray and gamma camera. These radiodiagnostic equipments can have negative impacts. That negative impact can damage the normal cells to become abnormal. Morever, further accumulation can even cause death if the amount of radiation exceeds the tolerable limits allowed by the radiation protection principles. This final project provide a simple calculation to determine the maximum absorption dose. This dose related to the critical value in which a human body can sustain from the radiation of X-ray equipments and gamma camera. To achieve the objective, we incorporate Matlab to obtain the numerical results. In this work, we insert a certain multiplying factors that correlate to the absorption dose and radiation protections from each equipment. We also discussed about the biological impacts that might occur in case the radiation dose exceeds the threshold value.